2019
DOI: 10.21511/ppm.17(4).2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Economic and management approach to defining effective projects for enterprise development under risks and uncertainty

Abstract: Enterprise development is dependent on the implementation of projects that contribute to improving economic performance. Considering this the need to apply the economic and management approach to the definition of effective projects under risks of reduced enterprise profitability due to the uncertain economic environment is justified. The study used scientific abstraction, formalization, causal relationship, time series analysis, variational range-based standardization, parameter minimization according to maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…With the rapid development of the Internet, enterprise economic management is gradually shifting towards data-driven and intelligent directions [8][9]. Data mining, as an effective data analysis technology, is widely applied in the field of enterprise economic management to improve decision-making efficiency, reduce risks, and enhance enterprise competitiveness [10][11].…”
Section: Enterprise Economic Management Based On Data Miningmentioning
confidence: 99%
“…With the rapid development of the Internet, enterprise economic management is gradually shifting towards data-driven and intelligent directions [8][9]. Data mining, as an effective data analysis technology, is widely applied in the field of enterprise economic management to improve decision-making efficiency, reduce risks, and enhance enterprise competitiveness [10][11].…”
Section: Enterprise Economic Management Based On Data Miningmentioning
confidence: 99%
“…At the same time, the formation of such a trajectory should take into account the external influences on the enterprise, the level of development of innovation potential, targets and orientation of the enterprise, which is set out in detail by the author in the works (Gavrysh, Dunska, Zhygalkevich, Kravchenko, 2019). In addition, the regulation of the trajectory in accordance with the targets of development should be based on the use of the results of systematic economic and managerial diagnostics, in the existing conditions, which allows to establish their inconsistency with the target level for management decisions to eliminate negative trends (Boiarynova, Kopishynska, Hryhorska, 2019;Gavrysh, Boiarynova, 2017).…”
Section: Organizational and Managerial Approach To Ensuring Innovative Developmentmentioning
confidence: 99%
“…In order to promote the development of green enterprise management, Liu (2022) proposed optimization suggestions for the financial management system through investigation [2]. Boiarynova et al (2019) monitored the dynamics of enterprise development and reduced the risk of management projects by evaluating the profitability dynamics of the production, management, and financial subsystems of the enterprise [3]. Song (2021) found that the centralized management of funds is a tool for allocating funds within the group and the coordinated management of the group's investment and financing.…”
Section: Introductionmentioning
confidence: 99%